ROLE OF FOLIAR APPLICATION WITH PLANT EXTRACTS, AND ADDING HUMIC ACID IN GROWTH OF Calendula officinalis AND ITS CONTENT FROM ZEAXANTHIN AND LYCOPENE - Al-Badri , Saja N. Al-Badri; Al-Amrani , Hussein A. Al-Amrani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The research was conducted at Research Station, College of Agricultural Engineering Sciences - University of Baghdad during fall seasons of 2021-2022 and 2022-2023 with the aim of studying the effect of foliar application with Moringa extract, yeast suspention, and adding humic acid on the vegetative and flowering growth of marigold plant and its content of plant pigments. A factorial experiment including three factors in (RCBD) with three replicates . First factor was foliar application with Moringa leaf extract at concentrations 4,6,8 % (M1,M2,M3), as well as yeast suspension at a concentration 5 and 10 g .L-1 (Y1,Y2), in addition to the control treatment (Y0), and Adding humic acid to the soil at concentrations 0 and 5 ml l-1 (H0,H1), respectively. The results showed a significant superiority for the interaction treatment M3Y2H1 in leaf area, plant and flower dry weight, and the content of Lycopene and Zeaxanthin for both seasons. It reached 75.92 dm², 23.81 g plant-1 , 0.520 g flower plant-1 , 22.95 µg g-1, and 47.27 µg g-1, respectively, for the first season, and 68.27 dm², 22.03 g plant-1, 0.477 g flower plant-1, 17.63 µg g-1, and 44.26 µg g-1, respectively, for the second season compared to the control treatment.